Reevaluating the Legal Status of Misyār Marriage: Contextual Insights from Figures of the Indonesian Ulema Council in Malang City - Rouf, Abd (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2024)
This paper explores the perspectives of figures from the Indonesian Ulema Council (MUI) of Malang City regarding the legal status of misyār marriage in contemporary contexts. As an empirical legal study, this research employs a conceptual and philosophical approach and utilizes maqāṣid al-sharī‘ah of Jamāluddīn ibn ‘Aṭiyyah by conducting interviews with two figures. The findings reveal that they consider misyār marriage permissible and valid under stringent conditions. First, the wife must willingly accept the absence of financial support from the husband. Second, the wife's obedience to the husband must remain intact, ensuring that whenever the husband expresses a need or desire, the wife is obligated to fulfill her marital duties. Misyār marriage is viewed as consistent with maqāṣid al-sharī‘ah due to its emphasis on avoiding adultery (zina), reflecting ḥifẓ al-nasl (preserving lineage) and ḥifẓ al-nasab (upholding the family heritage). Furthermore, when this type of marriage provides comfort for the couples, it embodies the values of sakīnah (tranquility), mawaddah (affection), and raḥmah (compassion), aligning with the evolving contexts and the changing needs of the partners. However, this perspective simultaneously raises new legal challenges in the context of Indonesian Islamic family law, which offers women-based protection in the ongoing discourse.